Offering surprises: TCA cycle regulation in Corynebacterium glutamicum - Bott, Michael (Trends in microbiology (Regular ed.), 2007)
Corynebacterium glutamicum, a Gram-positive soil bacterium, is used for the production of l-glutamate and l-lysine, both of which are derived from intermediates of the tricarboxylic acid (TCA) cycle. Recent studies have revealed that this amphibolic pathway is subject to complex regulation not only at the transcriptional level, but also at the post-transcriptional level. The latter involves serine/threonine protein kinase G and its target protein OdhI. Depending on its phosphorylation state, OdhI inhibits the 2-oxoglutarate dehydrogenase complex. This new type of TCA cycle control will be reviewed here together with regulation at the level of gene expression.